2017
DOI: 10.1111/1742-6723.12732
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography for head injuries in children: Change in Australian usage rates over time

Abstract: CTB use in head injuries did not increase during the study period, and rates of CTB were less than reported for North America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…While variation between hospitals, type of ED and country exists, the CTB rate at all sites was less than 20%, with an overall site adjusted rate of 11.2%. Overall imaging rates described in this prospective study are similar to rates described in an earlier retrospective Australasian PREDICT study between 2001 and 2010, suggesting little change over time . Australasian CTB rates are considerably lower and less variable than the paediatric CTB rates described in many other settings; in two large North American cohorts scanning rates across EDs varied between 19 and 58% (overall rate 36%) and 19.2 and 69.2% (35.3%), respectively.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…While variation between hospitals, type of ED and country exists, the CTB rate at all sites was less than 20%, with an overall site adjusted rate of 11.2%. Overall imaging rates described in this prospective study are similar to rates described in an earlier retrospective Australasian PREDICT study between 2001 and 2010, suggesting little change over time . Australasian CTB rates are considerably lower and less variable than the paediatric CTB rates described in many other settings; in two large North American cohorts scanning rates across EDs varied between 19 and 58% (overall rate 36%) and 19.2 and 69.2% (35.3%), respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Overall imaging rates described in this prospective study are similar to rates described in an earlier retrospective Australasian PREDICT study between 2001 and 2010, suggesting little change over time. 13 Australasian CTB rates are considerably lower and less variable than the paediatric CTB rates described in many other settings; in two large North American cohorts scanning rates across EDs varied between 19 and 58% (overall rate 36%) 19 and 19.2 and 69.2% (35.3%), 12 respectively. This latter PECARN study 12 found interhospital variation in the number of CTBs per ciTBI varied between 14.5 and 111.7; in our cohort this ranged from 5.9 to 11.4.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations